6ER-024 Immune checkpont inhibitors in pharmacological therapy. (2nd March 2018) - Jesus, M Martins de; Morgado, S; Alcobia, A; Morgado, M
Abstract : Background: The development of immunotherapy has proved to be a promising strategy in the treatment of cancer. The role of immune checkpoint inhibitors (ICIs) is highlighted. Purpose: To review the different ICIs available in clinical practice, analysing the authorised therapeutic indications and reporting the main adverse effects associated with these therapeutic agents. Material and methods: Bibliographic review of the Summary of Product Characteristics of ICIs authorised by the European Medicines Agency (EMA) and the United States Food and Drug Administration (FDA). A search for articles, published from 2015 to 2017, was also made in PubMed's electronic database. Results: Three ICIs are available in the Portuguese pharmaceutical market: ipilimumab, nivolumab and pembrolizumab. Ipilimumab (anti-CTLA-4) and pembrolizumab (anti-PD-1) are used in the treatment of advanced melanoma (AM) and may be used in association as described in phase I clinical trials. 1 Nivolumab is approved for the treatment of non-small cell lung cancer (NSCLC), and may be associated with ipilimubab for the treatment of AM. 2, 3 Avelumab, atezolizumab and durvalumab (anti-PD-1) have been approved by the FDA for the treatment of metastatic Merkel cell cancer, NSCLC and urothelial cancer, respectively. Several ICIs are under investigation for the treatment of other oncological conditions such as breast and prostate cancer among others. 4–6 These drugs are associated with inflammatory adverse effects known as immune-related adverse events (irAEs). Rash, pruritus, diarrhoea, colitis, hepatitis, endocrinopathy and pneumonitis are the most common irAEs associated with ICIs. The use of PD-1 inhibitors has demonstrated a lower incidence of irAEs when compared to those that block CTLA-4 such as ipilimumab. According to a phase 3 study, the combination of ipilimumab and nivolumab revealed a higher rate of irAEs than any approach in monotherapy. Similar results were published in a phase 3 study involving the combination of ipilimumab and pembrolizumab in patients with melanoma. 7 Conclusion: ICIs play a key role in the treatment of oncological diseases. Some of these drugs are still under investigation in order to evaluate their potential for other clinical indications. The safety of these drugs is considered their main challenge, presenting relevant adverse effects that require close monitoring by health professionals. References and/or Acknowledgements: 1. PMID:28729151. 2. PMID:28363334. 3. PMID:28889792. 4. PMID:27111907. 5. PMID:27138582. 6. PMID:25858804. 7. PMID:27367787. No conflict of interest